Menuju Realitas Peserta Didik yang Penuh Kreativitas - Siswadi Siswadi (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2018)
Abstract: Teachers are the main players in the implementation of education in the field. It is the teachers who carry out teaching and learning in schools and teaching success is the success of education in general, so that the creativity of teachers is necessary for students interested in understanding the lessons and foster creativity. In this paper, the discussion about the definition, characteristics, and strategies for teachers to develop the learning process of learning in the classroom into a creative learning and students will produce creative output as well. Keyword: The reality of Students and creativity.